Validasi Modul “SHARING” untuk Fasilitator Program Antiperundungan - Wenny Hikmah Syahputri; Amitya Kumara (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
The  purpose of this study to examine the module "SHARING" to improve knowledge of antibullying and presentation skills antibullying. The design used in this study was the one  group pretest-posttest design. Quantitative analysis was conducted through statistical test  using Paired t-test. The result showed that there is significant  improvement between pretest  and  posttest on knowledge antibullying (t=-6.254, p<0.01  ), as well as presentation skills of antibullying (t=-17.872, p<0.01) in the study participants. The conclusion is that the module "SHARING" can improve their knowledge of antibullying and presentation skills of antibullying.